2008
DOI: 10.2174/1875932700801010001
|View full text |Cite
|
Sign up to set email alerts
|

Starch and Cellulose as Fuel Sources for Low Temperature Direct Mode Fuel Cells

Abstract: This paper is a study about a direct mode fuel cell with a near-neutral-state and alkaline electrolytes. The aim of study was to develop a fuel cell, which operates directly by mixing the fuel with the electrolyte. This arrangement helps to avoid inserting membranes and additional bacterial cultures in fuel cell. The target is also to create a fuel cell with a capacity of few mWcm -2 with the starch as a fuel. Also, glucose and sorbitol have been tested as fuel for the fuel cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…However it was clearly indicated that the hydrolysation and the following concentrating methods have to be much improved to produce higher glucose concentrations in the hydrolysates. It was reported early on that pure glucose in a concentration of 1 M provides current density values from 5 (at RT) to 8 mAcm -2 (at 51 o C) with a voltage of 0.5 V [1,2]. Thus, the detected OCV and current density values with a lower glucose concentration in hydrolysates did not produce values equal to those reached earlier with pure glucose [1,2].…”
Section: Thermec 2009mentioning
confidence: 80%
See 4 more Smart Citations
“…However it was clearly indicated that the hydrolysation and the following concentrating methods have to be much improved to produce higher glucose concentrations in the hydrolysates. It was reported early on that pure glucose in a concentration of 1 M provides current density values from 5 (at RT) to 8 mAcm -2 (at 51 o C) with a voltage of 0.5 V [1,2]. Thus, the detected OCV and current density values with a lower glucose concentration in hydrolysates did not produce values equal to those reached earlier with pure glucose [1,2].…”
Section: Thermec 2009mentioning
confidence: 80%
“…In this study, an anode catalyst of alloyed platinum with palladium (Pt-Pd) and a combined cathode catalyst of cobalt porphyrin complex (CoTPP) and of spinel (MnCo 2 O 4 ) are tested in the test fuel cell with an alkaline electrolyte. It was reported earlier that several electro catalysts can not work well in near-neutral-state electrolytes (at pH 7.4) because of low electric conductivity values [17].…”
Section: Bioorganic Materials As a Fuel Sourcementioning
confidence: 97%
See 3 more Smart Citations